The Impact of International Students’ Social Adaptation on the Training Process in Higher Education - Liudmyla Pikulytska (Educational Challenges)
The article deals with the impact of international students’ social adaptation on the training process in higher educational institution. The article aims to highlight and analyze the main aspects of international students’ social adaptation as one of the effective factors that impact the quality of training. The tasks of the article are to study and characterize the features of the process of international students’ social adaptation (phases, types, components); to analyze challenges of social adaptation that international students meet; to introduce ways to overcome the problems of international students’ social adaptation in higher education.